1997
DOI: 10.1002/(sici)1098-2280(1997)30:2<161::aid-em9>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin C supplementation on biomarkers of oxygen radical generated damage in human volunteers with “low” or “high” cholesterol levels

Abstract: A human volunteer study was conducted to test the effect of vitamin C supplementation on biomarkers of oxygen radical-mediated damage in individuals with a range of serum cholesterol levels. A group of 48 non-smokers, 24 men and 24 women, was selected from a panel of over 100 volunteers to give as wide a range of serum cholesterol levels as possible. None of the volunteers was taking medication to control cholesterol levels and they maintained their normal dietary habits so as not to compromise their cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
3
11
1
2
Order By: Relevance
“…Some investigators have reported a reduction in ex vivo or in vivo DNA oxidation in lymphocytes after vitamin C supplementation in healthy volunteers [25,35,36], whereas others have shown no change [37] or even yielded mixed results with a decreased in some types of oxidized DNA bases and an increase in others [38,39]. However, this inconsistency is likely due to technical problems associated with gas chromatography-mass spectrometry analysis in some studies [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have reported a reduction in ex vivo or in vivo DNA oxidation in lymphocytes after vitamin C supplementation in healthy volunteers [25,35,36], whereas others have shown no change [37] or even yielded mixed results with a decreased in some types of oxidized DNA bases and an increase in others [38,39]. However, this inconsistency is likely due to technical problems associated with gas chromatography-mass spectrometry analysis in some studies [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the comet assay has been gaining acceptance due to its capacity to detect low levels of basal DNA damage without artifactual oxidation (48,57,58) (Table 2). A recent study examined DNA damage in lymphocytes with this assay (57). Nonsmoking subjects were given placebo, 60 and 6000 mg/day of vitamin C for 2 wk each, with 6 wk in between treatment periods.…”
Section: Human Supplementation Studiesmentioning
confidence: 99%
“…Vitamin C has been shown to significantly reduce lipid peroxide levels [39] and protect LDL-C from oxidation, thus facilitating LDL's normal binding to membrane receptors on the liver and therefore expedite its removal from the blood by LDL-C catabolic pathways. However, some researchers reported that vitamin C did not protect plasma lipids [40] or LDL [41,42] from oxidation and suggested that this is because vitamin C is hydrophilic and does not bind to lipoproteins [42]. Although the underlying mechanisms are not yet fully understood, it is reasonable to assume that the hypocholesterolemic properties of vitamin C are most profound when total serum cholesterol is very high [43].…”
Section: Resultsmentioning
confidence: 99%